In Vitro Passive eDNA Sampling Provides a Cost‐Effective Alternative for Large Scale Sample Collection - Samuel Thompson; Simon Jarman; Kingsley Griffin; Matthew Heydenrych; Julian Partridge; Tim Langlois (Environmental DNA)
ABSTRACT Passive sampling is an emerging method for environmental DNA (eDNA) sampling in aquatic environments. Passive eDNA collection methods are time efficient, inexpensive, and require minimal equipment, making them suited to high‐density sampling, especially in remote locations. Here we trial new passive eDNA sampling methods, which we term ‘in vitro passive eDNA sampling’; where a water aliquot is collected at a sampling location and passively sampled in a microcosm experiment, allowing for high‐density sampling while the researcher moves to other areas. Furthermore, we test whether agitating in vitro passive samples improves DNA yield and biodiversity estimations. We show that at a species level, in vitro passive sampling methods can return comparable species richness estimates to conventional filtration at both estuarine and inshore marine locations when analyzed as detections per unit of time taken to process the sample. In addition, agitating our in vitro passive samples improved DNA yields by an average of 2.2×as opposed to in vitro passive sampling without agitation, though both were significantly lower than filtration. These in vitro approaches to eDNA sampling will suit cost‐ and time‐sensitive biological surveys, where access to equipment is restricted and the need to complete high‐density sampling over large spatial scales is paramount.